2020
DOI: 10.1111/1467-9566.13079
|View full text |Cite
|
Sign up to set email alerts
|

Health technology identities and self. Patients’ appropriation of an assistive device for self‐management of chronic illness

Abstract: In recent years, assistive technologies have gained acceptance as tools for supporting chronically ill patients in achieving improvements in physical activity. However, various healthcare and sociological studies show contradicting results regarding the physical and social impact of using such devices. This paper explores real-time user appropriation of an assistive monitoring/tracking device, the pedometer, in a healthcare intervention, with a particular focus on the technology identities users attribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 43 , 62 , 64 In a study with patients with chronic obstructive pulmonary disease, users of a step counter felt stressful pressure to exercise, and had bad feelings about ‘losing steps’ when not wearing their device. 65 Toner suggests developing ways of using CHTs in a manner that counteracts the interests of other stakeholders, and repurposes CHTs for one's own true benefit, 29 while Vesnic-Alujevic et al even suggest developing CHTs on one's own. 58 Quantified self (QS) is a movement depicted as proactively counteracting the dominant data collection practices of powerful institutions and corporations, 66 pronouncing e.g., self-ownership and independent management of data (e.g., Open Humans 67 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 , 62 , 64 In a study with patients with chronic obstructive pulmonary disease, users of a step counter felt stressful pressure to exercise, and had bad feelings about ‘losing steps’ when not wearing their device. 65 Toner suggests developing ways of using CHTs in a manner that counteracts the interests of other stakeholders, and repurposes CHTs for one's own true benefit, 29 while Vesnic-Alujevic et al even suggest developing CHTs on one's own. 58 Quantified self (QS) is a movement depicted as proactively counteracting the dominant data collection practices of powerful institutions and corporations, 66 pronouncing e.g., self-ownership and independent management of data (e.g., Open Humans 67 ).…”
Section: Resultsmentioning
confidence: 99%
“… 76 Especially when CHTs become an integral part of users’ physical self-understanding, it may lead to stress when recommended standards of physical activity are not met, and a feeling of dependency. 65 Professional athletes, on the contrary, saw the practice of CHT use as an important and accepted part of their identity. 53 Datafication may help some people in finding a ‘stable identity in a liquid world’, raising questions about the extent of dependence CHT use may generate.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some clients reported negative reactivity to the self-monitoring, which was associated with less interest in using the tool again. Other studies also found that while self-monitoring can be motivating and helpful, it can also become a stressful activity that clients feel they have to comply with 27 . This all highlights the need to investigate how high-intensity self-monitoring tools such as ESM might be made less burdensome and stressful for users while still producing valuable information.…”
Section: Discussionmentioning
confidence: 99%
“…blood pressure tracking studied by Weiner & Will, 2018;Will et al, 2020). When professionals are readily available to aid the interpretation of data and to provide 'repair work' on the algorithms and outputs of digital devices (Schwennesen, 2019;Wienroth et al, 2020), the devices seem to be able to fulfil more of their therapeutic promises; they ease the burden on the health-care professionals by distributing some of the health-care work to technological devices that are emplaced in socio-technical arrangements of care (Schwennesen, 2019;Wienroth et al, 2020). Patients also engage in interventions that were not intended by the designers of the technologies, or by health-care professionals, in ways that reconfigure their therapeutic process and relationships (Piras & Miele, 2017).…”
Section: A Shift Towards Carementioning
confidence: 99%
“…Our findings confer that humans are not unquestioning recipients of data, but they actively generate and make sense of data (Bossen et al, 2019; Pantzar & Ruckenstein, 2017; Pink et al, 2017), which may lead them not only to question but also to implement small yet significant modifications in how they engage with their technologies and the other actors relevant to their fitness work—a practice we refer to as tinkering (Mol et al, 2010). Users often find ways to alter or appropriate (Wienroth et al, 2020) the outputs from their tracking devices to personalize them for their bodies and ‘optimize’ what the devices and data can do for them. This is sometimes accomplished with the aid of a personal trainer, who prescribes a course of action for the user, while other times users insert their own knowledge and expertise into the tinkering process.…”
Section: Tinkering: Calibrating For Carementioning
confidence: 99%